PENGARUH PENAMBAHAN SARI JAHE MERAH DAN SARI JERUK NIPIS TERHADAP MUTU MINUMAN SARI MELON (The Effect of Red Ginger Juice Addition and Lime Juice on The Quality of Melon Juice Drinks) - Gloria Febrine Valentin; Ismed Suhaidi; Era Yusraini (Universitas Sumatera Utara, 2018)
ABSTRACT The purpose of this research was to find the effect of red ginger juice addition and lime juice on the quality of melon juice drinks. The research was using completely randomized design with two factors, i.e addition of red ginger juice (S): (1%, 2%, 3%, 4%) and addition of lime juice (A): (1%, 2%, 3%, 4%) The addition of red ginger juice had a highly significant effect on total acid, vitamin C content, pH value, score value of flavour, score of taste, and hedonic of taste and had no significant effect on total soluble solid (TSS), hedonic values of color and flavour. The addition of lime juice had a highly significant effect on total acid, vitamin C content, pH value, score value of flavour, score of taste, and hedonic of taste and had no significant effect on total soluble solid (TSS), hedonic values of color and flavour. Interactions of the two factors had significant effect on pH value. The addition of red ginger juice of 1% and the addition of lime juice of 4% produced the best quality of melon juice drinks. Keywords : Melon, Red ginger, Lime, Fruit Juice Drinks ABSTRAK Penelitian ini dilakukan untuk mengetahui pengaruh penambahan sari jahe merah dan sari jeruk nipis terhadap mutu minuman sari melon. Penelitian ini menggunakan rancangan acak lengkap (RAL) faktorial dengan 2 faktor yaitu penambahan sari jahe merah (S): (1%, 2%, 3%, 4%) dan penambahan sari jeruk nipis (A): (1%, 2%, 3%, 4%). Penambahan sari jahe merah memberi pengaruh berbeda sangat nyata terhadap total asam, kadar vitamin C, nilai pH, nilai skor aroma, skor rasa, dan hedonik rasa serta memberi pengaruh berbeda tidak nyata terhadap total soluble solid (TSS), nilai hedonik warna dan aroma. Penambahan sari jeruk nipis memberi pengaruh berbeda sangat nyata terhadap total asam, kadar vitamin C, nilai pH, nilai skor aroma, skor rasa, dan hedonik rasa serta memberi pengaruh berbeda tidak nyata terhadap total soluble solid (TSS), nilai hedonik warna dan aroma. Interaksi kedua faktor memberi pengaruh berbeda nyata terhadap nilai pH. Penambahan sari jahe merah 1% dan penambahan sari jeruk nipis 4% memberikan pengaruh terbaik untuk mutu minuman sari melon. Kata kunci: Melon, Jahe Merah, Jeruk Nipis, Minuman Sari Buah